Retrospective analysis of postoperative complications following surgical treatment of ileal impaction in horses managed with manual decompression compared to jejunal enterotomy - Ruff, Jennifer; Zetterstrom, Sandra; Boone, Lindsey; Hofmeister, Erik; Smith, Caitlin; Epstein, Kira; Blikslager, Anthony; Fogle, Callie; Burke, Megan (Frontiers in Veterinary Science, 2023)
Objective: The objective of this study was to compare the occurrence of post-operative complications and survival to discharge in horses with ileal impactions resolved by manual decompression compared with jejunal enterotomy. Animals: 121 client-owned horses undergoing surgical correction of an ileal impaction at three teaching hospitals Materials and methods: Data from the medical records of horses undergoing surgical correction of an ileal impaction was retrospectively collected. Post-operative complications, survival to discharge, or post-operative reflux present were evaluated as dependent variables and pre-operative PCV, surgery duration, pre-operative reflux, and type of surgery were evaluated as independent variables. Type of surgery was divided into manual decompression (n=88) and jejunal enterotomy (n=33). Results: There were no significant differences in development of minor complications, development of major complications, presence of post-operative reflux, amount of post-operative reflux, and survival to discharge between horses that were treated with manual decompression and those treated with distal jejunal enterotomy. Pre-operative PCV and surgery duration were significant predictors of survival to discharge. Conclusions and clinical relevance: This study showed that there are no significant differences in post-operative complications and survival to discharge in horses undergoing distal jejunal enterotomy versus manual decompression for correction of ileal impaction. Pre-operative PCV and duration of surgery were found to be the only predictive factors of survival to discharge. Based on these findings, distal jejunal enterotomy should be considered earlier in horses with moderate to severe ileal impactions identified at surgery.